IMPROVING STUDENTS’ SPEAKING BY USING DRAMA TECHNIQUE - Friska Diniarty; Y. Gatot Sutapa Y; Eusabinus Bunau (Universitas Tanjungpura, 2018)
Abstract This research aimed as a research on improving the students’ speaking in class eleven multimedia of Vocational High School Mandiri Pontianak in Academic Year 2017/2018. The researcher used drama as technique in teaching speaking. The purpose of this research to improve the students’ speaking of the class eleven multimedia by using drama technique. The method of the research was the classroom action research, which consisted of 2 cycles. The subject of this research was students of class eleven multimedia of Vocational High School Mandiri Pontianak in academic year 2017/2018. The number of the students in this research was 24 students. The research was conducted to solve the problem encountered by the students. Most of the students were shy and afraid of making mistakes in terms of pronunciation. Most of them spoke with pauses. The result of this research had shown that drama technique can improve the students’ speaking. Besides, its systematic learning structures motivated the students to learn speaking, and maximized the students’ interaction during the learning process. The students’ speaking also increased after they tried to learn by using drama technique. They were more enthusiastic and confident in speaking practice. This implied that the implementation of drama technique gave positive effects to the improvement of students’ performance. Key words: Drama, Technique, Speaking